The International Master of Advanced Studies (MAS) in Sleep Medicine of the Universities of Bern and Svizzera Italiana - Bassetti, Claudio L. A.; Sohm, Felicitas; Adamantidis, Antoine; Schindler, Kaspar; Barazzoni, Fabrizio; Manconi, Mauro (Clinical and translational neuroscience, 2024)
Introduction: Sleep–wake circadian disorders (SWCDs) are very frequent and linked to major negative effects on the body, mental health, the brain, and on occupational and societal health. The prevention, diagnosis, and treatment of SWCDs and the promotion of sleep health require the sufficient education of general practitioners, specialists, and other health professionals. Unfortunately, education at pre- and postgraduate level is insufficient in most countries across the world. Aims and methods: This article describes the historical context, basic considerations, and methodological approach for the creation of the International Postgraduate Sleep Master by the University of Bern and Svizzera Italiana. Results: The postgraduate Master, which was launched in 2017, is a part-time, flexible course, taken over 2 ½ years, which targets health professionals, scientists, and technicians. After an initial introduction, which is the same for everybody (“common trunk”), the course can be individualized. The 12 modules of the Master include online lectures, schools, internships in a sleep center (in one of our 15 partner universities), case discussions and interactive sessions with students and internationally recognized experts from over 20 countries across the world, and culminates with a Master thesis. The program covers sleep–wake circadian biology; the management of SWCDs; disturbances of consciousness and sleep-related epilepsies; novel approaches in sleep medicine (e.g., clinical trials, telemedicine, data science, artificial intelligence); and topics of increasing relevance (e.g., neurodegenerative disorders, gender and diversity, sleep health, new technologies, artificial intelligence, professional and societal implications). Students are encouraged to also take “crash courses” in preparation for the national, European, and World sleep examinations. Conclusion: The Postgraduate University Sleep Master of the Universities of Bern and Svizzera Italiana offers a unique part-time, (mainly) virtual opportunity to acquire state-of the art knowledge, skills, and professional experiences to prepare for a clinical or scientific career in sleep medicine for physicians, scientists, and other health professionals.